COVID-19-Associated Pneumonia: Radiobiological Insights - François, Sabine; Helissey, Carole; Cavallero, Sophie; Drouet, Michel; Libert, Nicolas; Cosset, Jean-Marc; Deutsch, Eric; Meziani, Lydia; Chargari, Cyrus (Frontiers in Pharmacology, 2021)
The evolution of SARS-CoV-2 pneumonia to acute respiratory distress syndrome may be explained as being linked to a virus-induced “cytokine storm”, associated with systemic inflammation, coagulopathies, endothelial damage, thrombo-inflammation, immune system deregulation and disruption of angiotensin converting enzyme signaling pathways. While the anti-inflammatory effects of low dose irradiation have been exploited for a long time in the clinics, few recent physiopathological and experimental data suggested the possibility to modulate the inflammatory storm related to COVID-19 pulmonary infection by exposing patients to ionizing radiation at very low doses. Despite level of evidence is only preliminary, these preclinical findings open therapeutic perspectives and are discussed in this article.